Perceived Importance of and Attitude Towards Physical Education in Austrian Adolescents – the Role of Sex, Age and Weight Status - De Moraes-Ferrari, G (American Institute of Mathematical Sciences, 2025)
Physical education (PE) is often considered an ideal setting for the promotion of physical activity (PA) among adolescents and for the encouragement of an active lifestyle in adulthood. In order to achieve this goal, however, it is necessary to foster a positive attitude towards PE. The present study examined attitudes towards and the perceived importance of PE among Austrian adolescents. A total of 3011 adolescents (47.5% female) between 10 and 17 years of age completed a standardized questionnaire during regular school hours. In addition, body weight and height were measured. Overall, 78.5% stated that PE is important to them and 84.3% believed that PE positively affects their health and well-being. PE also motivated 68.4% of the participants to engage in leisure time PA, and 69.9% would like to have daily PE. Further, 91.0% reported a good relationship with their PE teacher while 68.6% considered themselves to be good at sports. Nevertheless, there was a significant decline in the perceived value of PE with increasing age, and among girls, as well as those with excess body weight, perceived PE to be less important. As these groups are particularly vulnerable for low PA levels, it is important to provide challenging and enjoyable experiences that foster a positive attitude towards PE. Ensuring positive experiences throughout students’ school careers could play a key role in promoting an active lifestyle later in life. © 2025 the Author(s)